Glycolic acid attenuates UVB-induced aquaporin-3, matrix metalloproteinase-9 expression, and collagen degradation in keratinocytes and mouse skin. Issue 10 (21st May 2019) - Tang, Sheau-Chung; Tang, Lee-Chun; Liu, Chin-Hung; Liao, Pei-Yun; Lai, Ji-Ching; Yang, Jen-Hung
Abstract : Ultraviolet-B exposure causes an inflammatory response, photoaged skin, and degradation of extracellular matrix proteins including collagen and elastin. The regulation of these genes was suggested as an important mechanism to attenuate skin aging. Glycolic acid (GA) is commonly present in fruits and recently used to treat dermatological diseases. We reported that GA slows down cell inflammation and aging caused by UVB. Little is known about GA retarding the skin premature senescence or how to impede these events. To investigate the potential of GA to regulate the expression of MMPs and collagen, GA was topically applied onto human keratinocytes and the C57BL/6J mice dorsal skin. In the present study, we demonstrated that GA reduced UVB-induced type-I procollagen expression and secretory collagen levels. GA reverted and dose-dependently increased the level of aquaporin-3 (AQP3), the expression of which was down-regulated by UVB. The UV-induced MMP-9 level and activity were reduced by GA pre-treatment. Concomitantly, GA reverted mitogen-activated protein kinase (MMP-9) activation and inhibited the extracellular signal-regulated kinase activation (p38, pERK) triggered by UVB. The animal model also presented that GA attenuated the wrinkles caused by UVB on the mouse dorsal skin. Finally, GA triggers the transient receptor potential vanilloid-1 (TRPV-1) channel to initiate the anti-photoaging mechanism in keratinocytes. These findings clearly indicated that the mechanisms of GA promote skin protection against UVB-induced photoaging and wrinkle formation. GA might be an important reagent and more widely used to prevent UVB-induced skin aging.